Transfusion Preparedness in the Labor and Delivery Unit: An Initiative to Improve Safety and Cost. Issue 5 (November 2021) - Benson, Ashley E.; Metcalf, Ryan A.; Cail, Kelly; Rollins, Mark D.; Warrick, Christine M.; Falkner, Dane; Clark, Erin A.S.; Nelson, Richard E.; Einerson, Brett D.
Abstract : OBJECTIVE: To evaluate patient safety, resource utilization, and transfusion-related cost after a policy change from universal type and screen to selective type and screen on admission to labor and delivery. METHODS: Between October 2017 and September 2019, we performed a single-center implementation study focusing on risk-based type and screen instead of universal type and screen. Implementation of our policy was October 2018 and compared 1 year preimplementation with 1 year postimplementation. Patients were risk-stratified in alignment with California Maternal Quality Care Collaborative recommendations. Under the new policy, the blood bank holds a blood sample for processing (hold clot) on patients at low- and medium-risk of hemorrhage. Type and screen and crossmatch are obtained on high-risk patients or with a prior positive antibody screen. We collected patient outcomes, safety and cost data, and compliance and resource utilization metrics. Cost included direct costs of transfusion-related testing in the labor and delivery unit during the study period, from a health system perspective. RESULTS: In 1 year postimplementation, there were no differences in emergency-release transfusion events (4 vs 3, P >.99). There were fewer emergency-release red blood cell (RBC) units transfused (9 vs 24, P =.002) and O-negative RBC units transfused (8 vs 18, P =.016) postimplementation compared with preimplementation. Hysterectomies (0.05% vs 0.1%, P =.44) and intensive care unit admissions (0.45% vs 0.51%, P =.43) were not different postimplementation compared with preimplementation. Postimplementation, mean monthly type and screen-related costs (ABO typing, antibody screen, and antibody workup costs) were lower, $9, 753 compared with $20, 676 in the preimplementation year, P <.001. CONCLUSION: Implementation of selective type and screen policy in the labor and delivery unit was associated with projected annual savings of $181, 000 in an institution with 4, 000 deliveries per year, without evidence of increased maternal morbidity. Abstract : A policy of selective type and screen in the labor and delivery unit was associated with cost savings without increased utilization of uncrossmatched blood or increased maternal morbidity.